Effect of planting Density on Growth and flowering of Chrysanthemum Grandiflorum cv. Euro under Syrian coastal conditions. (Latakia University Journal -Biological Sciences Series, 2022)
The objective of this work was to determine  the optimum planting density of Chrysanthemum cultivar " Euro" under  the Syrian coastal conditions .Rooted cuttings of Chrysanthemum were planted at five different planting densities(five treatments) T1: 10 * 15 cm, T2: 15 * 15 cm, T3: 15 * 20 cm, T4: 20 * 20 cm and T5: 20 * 30 cm with Three replicates for each  treatment (1m² for each replicate).The results showed an inverse relationship between planting density and vegetative growth parameters (plant height, number of branches per plant, number of leaves, and plant leaf area) as well as the flowering parameters (number  of flowering stems , number and quality of flowers per plant).The results also confirmed that the good development of the vegetative growth at low densities (T4 and T5) was associated with an increase in the plant dry mass, macronutrients (N:P:K) content and chlorophyll content which all had positive effects on flowering.These positive effects were notably reflected in the economic efficiency; T4 achieved the highest profitability coefficient (202.7%), with the best total profit (2250000 Syrian pounds/dunum).